Desiccation enhances phosphorylation of PSII and affects the distribution of protein complexes in the thylakoid membrane. Issue 3 (18th September 2014) - Gao, Shan; Gu, Wenhui; Xiong, Qian; Ge, Feng; Xie, Xiujun; Li, Jian; Chen, Weizhou; Pan, Guanghua; Wang, Guangce
<x xml:space="preserve">Abstract</x> Desiccation has significant effects on photosynthetic processes in intertidal macro‐algae. We studied an intertidal macro‐alga, Ulva sp., which can tolerate desiccation, to investigate changes in photosynthetic performance and the components and structure of thylakoid membrane proteins in response to desiccation. Our results demonstrate that photosystem II (PSII) is more sensitive to desiccation than photosystem I (PSI) in Ulva sp. Comparative proteomics of the thylakoid membrane proteins at different levels of desiccation suggested that there were few changes in the content of proteins involved in photosynthesis during desiccation. Interestingly, we found that both the PSII subunit, PsbS (Photosystem II S subunit) (a four‐helix protein in the LHC superfamily), and light‐harvesting complex stress‐related (LHCSR) proteins, which are required for non‐photochemical quenching in land plants and algae, respectively, were present under both normal and desiccation conditions and both increased slightly during desiccation. In addition, the results of immunoblot analysis suggested that the phosphorylation of PSII and LHCII increases during desiccation. To investigate further, we separated out a supercomplex formed during desiccation by blue native‐polyacrylamide gel electrophoresis and identified the components by mass spectrometry analysis. Our results show that phosphorylation of the complex increases slightly with decreased water content. All the results suggest that during the course of desiccation, few changes occur in the content of thylakoid membrane proteins, but a rearrangement of the protein complex occurs in the intertidal macro‐alga Ulva sp.